Anthropological studies in Chile: Local factors in the dynamics of a weak scientific institutionalization style (1875-1930) (Quinto Sol, 2021)
Despite the early impulse that the anthropological sciences received in Chile, very much in line with what happened in other Latin American countries, its institutionalization was interrupted towards the end of the 1930s. Our study’s findings suggest that this situation was not the result of the economic and social crises, which were typical of the period, but by the lack of interest shown by successive governments. This disinterest is reflected in the deficient material and institutional conditions available to anthropological studies, which would in turn impede their consolidation as a scientific discipline during the first half of the 20th century. By following proposals that highlight the potential of the category of style in the analysis of anthropologies developed in Latin America, the article explores the social context and material conditions which enabled the rise of anthropology at the local level, tracing its connections to State policy and its role in the national formation of alterities.
Keywords: weak style scientific institutionalization Anthropology; weak style; scientific institucionalization; Anthropology; scientific institutionalization